Irrigation reduction resistance mechanisms in the rapid fruit growth stage of pears (Pyrus communis L.) (2016)
Plants adopt physiological defense mechanisms to counteract droughts. In Colombia, there is no information for these mechanisms in pears (Pyrus communis L.), cv. Triunfo de Viena. Therefore, the present study aimed to analyze the hydric conditions of this plant in order to determine if it has developed a mechanism to avoid, reduce, or tolerate water stresses as a defense. This experiment used a pear crop located in the municipality of Sesquile (Colombia), with 16-year-old trees that were subjected to three irrigation treatments: a control that received 100% of this crop's evapotranspiration (100%ETc), and 73%ETc and 53%ETc treatments were irrigated at 73% and 53% of crop's evapotranspiration, respectively, for the entire rapid fruit growth period of 2012 to 2013. The results indicated that the irrigation reduction in 53%ETc treatment present an adaptive mechanism in the trees, with a structural change in the cellular wall that allowed for 47% water savings in this fruit growth stage.